2003
DOI: 10.1002/gps.870
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and phenomenological comparisons of delusional and non‐delusional major depression in the Chinese elderly

Abstract: Our findings were grossly concordant with previous Western reports, and highlight the importance of identifying the delusional subgroup of depressive patients because of the higher risk of suicide attempt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 23 publications
1
32
2
6
Order By: Relevance
“…On the other hand, two studies [15,22] found no differences regarding psychomotor disturbances. Parker et al [26,27,28,29] have found that delusional melancholics manifested a higher level of psychomotor disturbances (agitation or retardation) as compared to non-delusional melancholics.…”
Section: Clinical Characteristicsmentioning
confidence: 90%
See 3 more Smart Citations
“…On the other hand, two studies [15,22] found no differences regarding psychomotor disturbances. Parker et al [26,27,28,29] have found that delusional melancholics manifested a higher level of psychomotor disturbances (agitation or retardation) as compared to non-delusional melancholics.…”
Section: Clinical Characteristicsmentioning
confidence: 90%
“…Meyers and Greenberg [6] found that PDs had a statistically significant older age of depression onset and renewed the interest in this variable. On the other hand, Nelson et al [18], Baldwin [15] and Lee et al [22] have not found any difference between the two groups regarding age at onset of the disorder. Gournellis et al [16] reported that the PDs of the sample had, indeed, an older age at onset.…”
Section: Clinical Characteristicsmentioning
confidence: 95%
See 2 more Smart Citations
“…26,27 One study found that delusional depressives' risk for suicide attempts was much higher than that of nondelusional depressives. 28 Another report described a case of a patient receiving IFNβ-1a therapy for MS who developed acute delirium, delusion, and depression that ceased with treatment discontinuation. 15 This patient had a history of depression prior to interferon therapy.…”
Section: Discussionmentioning
confidence: 99%